The first movie projector arrived in Venezuela 130 years ago (Mayéutica Revista Científica de Humanidades y Artes, 2026)
On July 11, 1896, businessman Luis Manuel Méndez brought the vitascope to Venezuela, an invention by American Thomas Alva Edison, which was used days later to make “the first projection” in the country. The first featurelength fiction film made in the country was La dama de las cayenas (1916), directed by Enrique Zimmermann. Later, Edgar Anzola directed La trepadora (1924), based on the novel of the same name by writer Rómulo Gallegos.
Keywords: Venezuelan cinema; vitascope; Manuel Trujillo Durán; Amábilis Cordero